P1335MALNUTRITION, INFLAMMATION, AND ANEMIA SYNERGISTICALLY IMPACT VASCULAR ACCESS FAILURE IN PATIENTS WITH FIRST-TIME ARTERIOVENOUS FISTULA FORMATION. (6th June 2020) - Hara, Masaki; Saiki, Naozumi; Suzuki, Hiroki; Ubukata, Masamitsu; Asao, Rin; Nakamura, Yuya; Nakamura, Masayuki; Ohsawa, Isao; Gotoh, Hiromichi
Abstract: Background and Aims: There are several reports that the initial (within one year) failure of vascular access (VA) is 2–53% in several countries. Malnutrition alone, inflammation alone, and anemia alone are factors that have a well-known relationship to VA failure. We believe that the relationship of these risk factors to VA failure is a complex one. Therefore, we evaluated whether the addition of these factors had a synergistic impact on VA failure. Method: This longitudinal cohort study sought to confirm the effects of malnutrition, inflammation, and anemia on VA failure. We included 177 patients with chronic kidney disease (CKD) with first-time arteriovenous fistulas who were treated from January 2013 to December 2017. VA failure was defined as a new onset of VA obstruction or the need for percutaneous transluminal angioplasty. Albumin (Alb), C-reactive protein (CRP), and hemoglobin (Hb) were studied as indicators for malnutrition, inflammation, and anemia, respectively. Each highest (CRP) or lowest (Alb and Hb) interquartile range (IQR) group was assigned 1 point (as a risk score). The cumulative VA failure rate was analyzed by the Kaplan-Meier method, which stratified the study cohort into four groups according to the risk scores (0–3). We assessed whether the lowest IQR group of Hb and Alb, and the highest IQR group of CRP were associated with VA failure. To determine this, we used a univariable Cox proportional hazards regression analysis to calculate the hazard ratio (HR) and its 95% confidence interval (CI). A multivariable Cox proportional hazards regression analysis was used to evaluate the association between the risk score and VA failure, with adjustment for age, sex, presence or absence of diabetes mellitus, value of calcium phosphate products, preoperative vein diameter, and intraoperative vascular assessment scores. Results: The average observational period was 1.6±1.4 years. The incidence of VA failure was 30.5% (54 patients). Cumulative VA failure was significantly higher in patients who had more than two risk scores, as compared to the patients who did not have any risk score (Figure). The univariate Cox regression analysis showed that Alb, CRP, and Hb were significantly associated with VA failure (HR, 2.00; 95% CI, 1.08–3.71 for Alb and HR, 2.21; 95% CI, 1.15–4.13 for CRP and HR, 1.96; 95% CI, 1.02–3.63 for Hb), respectively. The presence of more than two risk scores was significantly associated with VA failure (HR, 4.68; 95% CI, 1.07–18.5 for the patients with two risk scores and HR, 4.72; 95% CI, 1.32–17.2 for the patients with three risk scores). Conclusion: Malnutrition, inflammation, and anemia independently and synergistically affect VA failure. In clinical settings, we need to be aware of the presence of malnutrition, inflammation, and anemia to better prevent VA failure.